OPTIMASI DESAIN SHELL AND TUBE HEAT EXCHANGER TIPE SINGLE SEGMENTAL BAFFLE DENGAN VARIASI JUMLAH BAFFLE DAN POTONGAN BAFFLE MENGGUNAKAN METODE COMPUTATIONAL FLUID DYNAMIC - Fajri, Ahmed; Saputra, Trisma Jaya; Dewi, Rany Puspita (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
The heat exchanger is a device used to transfer heat between two process streams. In general, the flow that occurs in shell and tube heat exchangers is parallel flow or counter flow. To change the flow in the shell and tube heat exchanger into the cross flow, baffles can be added. The ideal cutting for baffle cutting is taken 20% to 35% of the inner diameter of the shell while the baffle distance is one-fifth of the inside diameter (ID) of the shell or 2 inches. Shell type